2005
DOI: 10.1161/01.cir.0000153847.47301.80
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Self-Assembling Peptide Nanofibers Create Intramyocardial Microenvironments for Endothelial Cells

Abstract: Background-Promoting survival of transplanted cells or endogenous precursors is an important goal. We hypothesized that a novel approach to promote vascularization would be to create injectable microenvironments within the myocardium that recruit endothelial cells and promote their survival and organization. Methods and Results-In this study we demonstrate that self-assembling peptides can be injected and that the resulting nanofiber microenvironments are readily detectable within the myocardium. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
401
0
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 535 publications
(413 citation statements)
references
References 25 publications
4
401
0
8
Order By: Relevance
“…Cardiomyocytes from 1-day-old Sprague-Dawley pups (Charles River Laboratories) were obtained as described in ref. 12. The resulting cell pellet was resuspended in sucrose or self-assembling peptides for in vitro and in vivo studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiomyocytes from 1-day-old Sprague-Dawley pups (Charles River Laboratories) were obtained as described in ref. 12. The resulting cell pellet was resuspended in sucrose or self-assembling peptides for in vitro and in vivo studies.…”
Section: Methodsmentioning
confidence: 99%
“…On exposure to physiological osmolarity and pH, the peptides rapidly assemble into small nanofibers (Ϸ10 nm) that can be injected into the myocardium to form 3D cellular microenvironments (11,12). These peptide nanofiber microenvironments recruit a variety of cells including vascular cells (12).…”
mentioning
confidence: 99%
“…2,8,54,55 Further, this approach could be used to assemble the nanofibers in vivo to create an injectable scaffold for tissue repair 56 ; however, competition with natural amphiphiles present in vivo could complicate this application. While this approach creates nanofibers of the smallest scale (5-8 nm), the fabrication process is a challenging technique, limited to a few polymers, and can only create short fibers with lengths of one to several mm.…”
Section: 54mentioning
confidence: 99%
“…et al demonstrated that RADA16-II peptides rapidly gel when mixed with sterile sucrose solution. The resulting hydrogel created a microenvironment in the myocardium which promoted vascular cell recruitment and favored injected cell survival [63]. Then, Lin Y.D.…”
Section: Hydrogels In Cell-based Therapiesmentioning
confidence: 99%